2021
DOI: 10.3390/microorganisms9040801
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation and HPV-Associated Head and Neck Cancer

Abstract: Head and neck squamous cell carcinoma (HNSCC), especially oropharyngeal squamous cell carcinoma (OPSCC), has recently been found to be significantly associated with human papillomavirus (HPV) infection. The incidence of OPSCC has been increasing and surpassed the number of cervical cancer cases in the United States. Although HPV-associated OPSCC has a relatively better prognosis than HPV-negative cancer, approximately 20% of HPV-associated HNSCC patients show a poor prognosis or therapeutic response, and the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 111 publications
0
16
0
Order By: Relevance
“…Among the more than 200 existing HPVs, high-risk genotype (such as HPV16 and HPV18) persistent infections progress into cancer, and in the majority of HPV-driven carcinomas, type 16 is involved [ 9 ]. Most of the HPV16-induced head and neck cancers affect the palatine tonsils, that often metastasize to nearby lymph nodes [ 10 , 11 ]. Crucial in the pathogenesis of HPV-driven carcinomas is the expression of early genes-encoded E6 and E7 oncoproteins which, by targeting host cell tumor suppressors p53 and pRB, provide the infected keratinocyte with a growth advantage, with enhanced proliferation rate, impaired apoptosis and progressive immune evasion [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the more than 200 existing HPVs, high-risk genotype (such as HPV16 and HPV18) persistent infections progress into cancer, and in the majority of HPV-driven carcinomas, type 16 is involved [ 9 ]. Most of the HPV16-induced head and neck cancers affect the palatine tonsils, that often metastasize to nearby lymph nodes [ 10 , 11 ]. Crucial in the pathogenesis of HPV-driven carcinomas is the expression of early genes-encoded E6 and E7 oncoproteins which, by targeting host cell tumor suppressors p53 and pRB, provide the infected keratinocyte with a growth advantage, with enhanced proliferation rate, impaired apoptosis and progressive immune evasion [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, nine FDA-approved agents, representing four epigenetic targets (DNMT, HDAC, IDH, and EZH2), are used for the treatment of a variety of cancers, and several drugs that target epigenetic mechanisms are currently in clinical trials [ 113 ]. Many studies have reported that HPV-negative HNSCC has lower DNA methylation levels than HPV-positive HNSCC, which harbors distinctly hypermethylated genomes [ 114 ]. Thus, researchers expect that HPV-positive HNSCC will have a more robust response to epigenetic targeted therapy.…”
Section: Current Targeted Therapy For Head and Neck Cancermentioning
confidence: 99%
“…Methylome analyses of HPV-positive cancers revealed differences in DNA methylation compared to matching normal tissue or HPV-negative tumors and transfection studies have confirmed that the E6 and E7 oncoproteins provoked hypermethylation tumor suppressor genes and hypomethylation of proto-oncogenes [ 31 , 32 , 108 , 109 , 110 , 111 , 112 , 113 , 114 ]. Both these viral proteins have been shown to upregulate the expression of DNMT1.…”
Section: Oncoviruses and Host Cell Dna Methylationmentioning
confidence: 99%